C4 Protein of Sweet Potato Leaf Curl Virus Regulates Brassinosteroid Signaling Pathway through Interaction with AtBIN2 and Affects Male Fertility in Arabidopsis - Bi, Huiping; Fan, Weijuan; Zhang, Peng (Frontiers in Plant Science, 2017)
Sweepoviruses have been identified globally and cause substantial yield losses and cultivar decline in sweet potato. This study aimed to investigate the interaction between sweepovirus and plant host by analyzing the function of the viral protein C4 of Sweet potato leaf curl virus-Jiangsu (SPLCV-JS), a sweepovirus cloned from diseased sweet potato plants in East China. Ectopic expression of the C4 in Arabidopsis altered plant development drastically with phenotypic changes including leaf curling, seedling twisting, deformation of floral tissues and reduction of pollen fertility, and seed number. Using bimolecular fluorescence complementation analysis, this study demonstrated that the SPLCV-JS C4 protein interacted with brassinosteroid-insensitive 2 (AtBIN2) in the plasma membrane of Nicotiana benthamiana cells. The C4 AtBIN2 interaction was further confirmed by yeast two-hybrid assays. This interaction led to the re-localization of AtBIN2-interacting proteins AtBES1/AtBZR1 into the nucleus which altered the expression of brassinosteroid (BR)-response genes, resulting in the activation of BR-signaling pathway. The interaction of SPLCV-JS C4 and AtBIN2 also led to the down-regulated expression of key genes involved in anther and pollen development, including SPROROCYTELESS/NOZZLE, DEFECTIVE IN TAPEL DEVELOPMENT AND FUNCTION 1, and ABORTED MICROSPORES, which caused abnormal tapetal development, followed by defective exine pattern formation of microspores and pollen release. Consequently, male fertility in the C4 transgenic Arabidopsis was reduced. The present study illustrated how the sweepovirus C4 protein functioned in host cells and affected male fertility by interacting with the key components of BR-signaling pathway.